Constraining RS models by future flavor and collider measurements: a snowmass whitepaper - Agashe, Kaustubh; Bauer, Martin (Arxiv, 2013)
Randall-Sundrum models are models of quark flavor, because they explain the hierarchies in the quark masses and mixings in terms of order one localization parameters of extra dimensional wavefunctions. The same small numbers which generate the light quark masses suppress contributions to flavor violating tree level amplitudes. In this note we update universal constraints from electroweak precision parameters and demonstrate how future measurements of flavor violation in ultra rare decay channels of Kaons and B mesons will constrain the parameter space of this type of models. We show how collider signatures are correlated with these flavor measurements and compute projected limits for direct searches at the 14 TeV LHC run, a 14 TeV LHC luminosity upgrade, a 33 TeV LHC energy upgrade, and a potential 100 TeV machine. We further discuss the effects of a warped model of leptons in future measurements of lepton flavor violation.
Gesehen am 10.01.2018